Analisis Daya Saing Ekspor Komoditas Karet Alam Indonesia ke 10 Negara Tujuan - Rahmawati, Tiara; Abadi, Slamet; Wijaya, I Putu Eka (Program Studi Agribisnis, Fakultas Pertanian, Universitas Singaperbangsa Karawang, 2024)
ABSTRACT Natural rubber is an agricultural commodity that has advantages and potential competitiveness. Indonesia has the largest area of natural rubber plantations, but has not been able to make Indonesia the largest rubber exporting country in the world. Land productivity in Indonesia is still low and the quality of natural rubber produced is less than optimal. Demand for rubber in the world is increasing, and the intense competition between Indonesia's natural rubber exports and competing countries shows that it is necessary to increase competitiveness for Indonesia to be able to compete and survive in the international market. The research objectives are to analyze market structure, comparative advantages, and the position of Indonesia. This research is quantitative research. Secondary research data. Data analysis used the Herfindahl Index (HI), Revealed Comparative Advantage (RCA) and Trade Specialization Index (ISP). The HI result of 0.1362 shows that the market structure of the five exporting countries has an oligopoly market structure. The comparative advantage results show that Ivory Coast produces the highest RCA of 81.9, Thailand 29.6, Indonesia 28.1, Vietnam 6.0 and Malaysia 5.7 This shows that these five countries have strong competitiveness in the 10 destination countries. The ISP results show that Indonesia is at the maturity stage, 0.975 and is in a position as an exporter of natural rubber in the world.